Lectura crítica de estudios diagnósticos. - Sánchez Sánchez, Juan Antonio; Menárguez Puche, Juan Francisco (AMF: Actualización en Medicina de Familia, 2022)
The article "Critical reading of diagnostic studies" highlights the importance of critically reading validation studies of diagnostic tests. It mentions that the most common design is the cross-sectional validation study of diagnostic tests, where a test is compared to a reference test in patients suspected of having a health problem. It also mentions tools such as the STARD guideline and the QADAS-2, which help evaluate the quality of diagnostic studies. Additionally, key aspects to consider when reading these studies are highlighted, such as the spectrum of included patients, sample size, the selected gold standard, and the independent and blinded performance of the tests. The text also provides information on important aspects to consider in the validation of signs of semiology, such as a careful description of the patient selection process and sample size calculation. The STARD initiative is mentioned, which ensures the quality of diagnostic test validity studies, and a table describing the most common biases in these studies is provided.